From living apart to living together: Do children born before the current partnership matter? - Roselinde van der Wiel; Clara Helena Mulder; Helga de Valk (Comparative Population Studies (CPoS), 2020)
This study examines the association between having children born before the current partnership and women's and men's likelihood of transitioning from living apart together (LAT) to co-residing. LAT partnerships are common among individuals with pre-partnership children, but have so far been under-researched. Our study not only focuses on those in LAT relations, but also takes the different pathways to becoming a single parent into account. Event-history analysis was performed using waves 1-4 from the Netherlands Kinship Panel Study. The results indicate that separated and widowed mothers were less likely to transition to co-residence with their LAT partner than childless women who had previously been in a co-residential union. Mothers who had previous out-of-union children were found to be even less likely to enter co-residence. Results were mostly similar for men and women. The only exception was the effect of being widowed with children; for men this resulted in higher chances of transitioning to co-residence with a new partner whereas for women the chances were lower. The findings suggest that individuals' parenthood and union histories are associated with the development of their later partnerships, and that these patterns vary by gender. Given contemporary and future patterns of partnership separation, our study provides insights for better understanding how LAT relations develop for different sub-populations.
urn:nbn:de:bib-cpos-2020-07en9
Keywords: 300; Living apart together; Transition to co-residence; Re-partnering; Children; Single parents